Alat Ukur Jarak dan Sudut Kemiringan Konstruksi Tangga Bangunan Berdasarkan Aspek Ergonomi Berbasis Arduino - Kusnadi; Muhammad Akbar Hariyono; Hafiz Al Farizi (Universitas Muhammadiyah Surabaya, 2026)
This Arduino-based stair construction distance and inclination angle measuring tool is designed to meet the need for accurate, fast, and ergonomic measurements in building construction processes. By utilizing the US-100 ultrasonic sensor and the MPU-6050 accelerometer sensor, this tool can measure vertical and horizontal distances and the inclination angle of stairs in real-time, then display the results digitally on an LCD screen. The design of this tool aims to overcome the limitations of manual measuring tools that are prone to human errors, such as reading inaccuracies or improper tool placement. In the context of ergonomics, this tool ensures that stair construction meets comfort and safety standards, such as an ideal inclination angle between 25°–42°, a stair riser height of 14–20 cm, and a tread width of 22.5–30 cm. The tool's operation process starts from sensor initialization, conversion of raw data into measurable values, data validation, to the display of results on the LCD, with a loop system that allows repeated measurements without manual reset. Furthermore, this tool is also designed to facilitate use by construction workers, inspectors, or even people with disabilities, with a clear, ergonomic, and responsive display. By integrating digital technology and ergonomic principles, this tool not only improves measurement accuracy but also time efficiency, work safety, and user comfort, thereby contributing to the development of a more inclusive and sustainable infrastructure.